STATUS MIKROBIOLOGIS DAGING BROILER DI PASAR TRADISIONAL KABUPATEN PRINGSEWU - Lasmi Ken Utari; Rr. Riyanti; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
Laying chicken is a type of extremely popular poultry developed by small farmers. Laying chicken (layerThis research aimed to determinemicrobiologic status observation on the broiler chicken of the traditional markets in the regency of Pringsewu. The study was conducted from September—October 2015 in the Laboratory Veteriner Office of Lampung. The study used a random sampling technique and used 20 samplesfrom 7 traditional markets.Parameters of microbiologic status observed total plate count, E. coli, dan Salmonella sp..Microbiologic status data were analyzed using binomial test concern their each parameters. The result showed that total plate count (TPC), Salmonella sp.and E.coli was not excess with standard. The broiler chicken microbiology status of the traditional markets in Pringsewu regency was not excess with benchmarks published by the National Standardization Agency (NSA) 7388:2009. (Keywords:broiler meat, total plate count, E. coli, Salmonella sp., traditional markets)